A STUDY ON GROWTH AND DEVELOPMENT OF HEALTH INSURANCE IN INDIA IN THE POST PRIVATIZATION ERA - Rath, Jyoti Prakash; Sahu, Maheshwar (International Journal of Research -GRANTHAALAYAH, 2017)
Health Insurance in India emerges in the year 1999 with the introduction of IRDA bill in the floor of Parliament. In the post-privatization era, health insurance segment developed slowly and steadily. The penetration of insurance sector in Non-Life insurance is kept on increasing since 2001. In order to portray the journey of health insurance sector in India, it is required to show the growth and development of this sector in the country. The present study is intended to evaluate the growth and development of the health insurance sector in India in the post-privatization era. Data are collected mainly from secondary sources. Such data are analyzed and represented suitable through the help of tables, diagrams and charts. From the study, it is concluded that there is a significant upward trend in the growth of health insurance industry in India both at public and private sector after privatization. If this trend continues by keeping other factors constant, then the health insurance business would touch to Rs 20000 crores in the financial year 2016-17 contributed at least 60% by public sector and rest 40% by both private insurers and standalone health insurers.